Short- and long-term outcome of allogeneic stem cell transplantation in infants: A single-center experience over 20 years - Miśkiewicz-Bujna, Justyna; Miśkiewicz-Migoń, Izabella; Szmit, Zofia; Przystupski, Dawid; Rosa, Monika; Król, Anna; Kałwak, Krzysztof; Ussowicz, Marek; Gorczyńska, Ewa (Frontiers in Pediatrics, 2022)
Abstract Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a treatment method for a wide range of malignant and non-malignant diseases. Infants constitute a distinct patient group, especially due to their organ immaturity and differences in drug metabolism. The present paper aims to analyse the short- and long-term outcomes after allo-HSCT in infants. Material and methods In the study period, 67 patients under 12 months of age underwent allo-HSCT. This study is a retrospective analysis of patient medical records, in the form of paper and electronic documentation. Results The probability of 5-year OS was 69% and 72% in patients with malignant and non-malignant diseases, respectively. The allo-HSCT from a matched donor was associated with improved OS in comparison to haploidentical donor (0.8 vs 0.58%, p=0.0425). The overall incidence of acute graft-versus-host disease (aGVHD) was 59.3%, and grade III–IV aGVHD was diagnosed in 23% of patients. The 100-day non-relapse mortality (NRM) in the study cohort was 17.9%, while the 5-year NRM was 26.9%. Among the causes of NRM, infections occurred in 83.3% of patients, and aGVHD in 16.3% of individuals. Twenty-two children (32.8%) required hospitalization in the paediatric intensive care unit (PICU). The median length of PICU hospitalization was 6 days (range 1 to 12 days). Late sequelae diagnosed during post-transplant surveillance included ocular disorders in 26.8% of patients, cardiac complications in 4.4%, as well as endocrinopathy with short stature (<3rd percentile) in 37.2% and overt hypothyroidism in 35.4%. In the long-term perspective, 83.3% of survivors were able to attend a regular school. Conclusions Improvements in unrelated donor availability, and better supportive care resulted in better outcomes. Management of infant allo-HSCT recipients requires the formation of multi-disciplinary specialist teams. In addition, the role of parental empowerment must be acknowledged; for example, in speech therapy and rehabilitation.